Brain metastasis of hepatocellular carcinoma detected after liver transplantation Metástase cerebral de carcinoma hepatocelular após transplante de fígado - Alex Vianey Callado França; Ana Martinelli; Orlando Castro e Silva Jr. (Arquivos de Gastroenterologia, 2004)
AIM: We report the case of a patient with hepatocellular carcinoma submitted to liver transplantation, who subsequently manifested tumor recurrence initially as brain metastasis. CASE DESCRIPTION: A 48-year-old male cirrhotic patient with hepatitis C infection, and two focal hepatic lesions, had a cytologic and histologic diagnosis of hepatocellular carcinoma. Before transplant, he was submitted to adjuvant treatment with a combination of arterial embolization and intratumoral ethanol injection. In the 3rd month post-liver transplantation, the patient developed headache, nausea and vomiting, without any neurological impairment. Brain computed tomography and magnetic resonance imaging identified an expansive hypervascular lesion with internal bleeding. Evaluation of the surgical explant revealed macroscopic invasion of portal vessels. CONCLUSION: Brain metastasis of a hepatocellular carcinoma after liver transplantation may occur. This metastasis may have occurred before or soon after the transplant. Patients with hepatocellular carcinoma, awaiting liver transplant, should be screened for cerebral metastasis. Vascular invasion may indicate hematogenic dissemination of the tumor. OBJETIVO: Relatar o caso de paciente com carcinoma hepatocelular submetido a transplante de fígado, que subseqüentemente manifestou recurrência tumoral em cérebro após o transplante. DESCRIÇÃO DO CASO: Homem de 48 anos de idade, com cirrose hepática secundária à infecção pelo vírus da hepatite C, com duas lesões focais hepáticas diagnosticadas como carcinoma hepatocelular pela citologia e histologia. Antes do transplante, foi submetido a tratamento coadjuvante com embolização da artéria hepática e injeção intra-tumoral de etanol. No terceiro mês pós-transplante, o paciente apresentou cefaléia, náuseas e vômitos, sem déficit neurológico focal. Tomografia computadorizada e ressonância magnética de crânio identificaram lesão expansiva hipervascular com sangramento interno. Avaliação da peça cirúrgica do transplante de fígado evidenciou invasão tumoral macroscópica da veia porta. CONCLUSÃO: A metástase cerebral de carcinoma hepatocelular após transplante de fígado pode ocorrer antes ou logo após a cirurgia. Pacientes, em lista para transplante de fígado, devem ser investigados para presença de metástase cerebral. Invasão vascular pode indicar disseminação tumoral hematogênica.